(untitled) (Huellas, 2026)
Food security is a key aspect of community participation processes, as it has an integrative capacity and promotes the practice of urban agriculture. The purpose of the research was to document the community’s experience with agriculture from a food security perspective, involving the residents of the El Mirador community in the Usme locality (Bogotá). To achieve this, various workshops, field visits, and collaborative activities were conducted in community-created gardens. The information collected was analyzed using a participatory approach, which enabled the inductive construction of analytical categories. Participants highlighted that food security represents an economic and well-being opportunity for families while fostering community participation spaces based on respect, peace, and well-being. Urban agriculture has become a mechanism for integration and coexistence, improving communication and encouraging an environmental approach aimed at promoting actions for the environment. This effort seeks to contribute, at a community scale, to solving the city’s food supply challenges. Furthermore, it serves as a way to make use of spaces that have resisted urbanization and gentrification processes in Bogotá.